-(4y+3)-(-3y-6)=-5

Simple and best practice solution for -(4y+3)-(-3y-6)=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(4y+3)-(-3y-6)=-5 equation:


Simplifying
-1(4y + 3) + -1(-3y + -6) = -5

Reorder the terms:
-1(3 + 4y) + -1(-3y + -6) = -5
(3 * -1 + 4y * -1) + -1(-3y + -6) = -5
(-3 + -4y) + -1(-3y + -6) = -5

Reorder the terms:
-3 + -4y + -1(-6 + -3y) = -5
-3 + -4y + (-6 * -1 + -3y * -1) = -5
-3 + -4y + (6 + 3y) = -5

Reorder the terms:
-3 + 6 + -4y + 3y = -5

Combine like terms: -3 + 6 = 3
3 + -4y + 3y = -5

Combine like terms: -4y + 3y = -1y
3 + -1y = -5

Solving
3 + -1y = -5

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -1y = -5 + -3

Combine like terms: 3 + -3 = 0
0 + -1y = -5 + -3
-1y = -5 + -3

Combine like terms: -5 + -3 = -8
-1y = -8

Divide each side by '-1'.
y = 8

Simplifying
y = 8

See similar equations:

| -54=2(y+6) | | 9(t-4)+6t=5(3t+4)-13 | | 9x-42=x-15 | | p^4-k^4=0 | | 5(4x-6)=-90 | | 4sp^4-4sk^4=0 | | -(7y+4)-(-6y-5)=0 | | 6(-2x-3)=-102 | | X-7.8=-6.9 | | 3(2x+7)=-9 | | 4=4+y | | -4(2x-6)=5x+24-7x | | 0=4+y | | 9i^22= | | -r+16r=-15 | | 27v^3+64=0 | | .50x=9 | | 12p-9p-p=16 | | y=4(-3)-3 | | 20k-15k+-k+2=10 | | -2=.25a-13 | | 2k+4k-1=17 | | 2x^2-12x-3=0 | | y+31=16 | | -3(x-1)=7 | | 19+x=51 | | -2(-4x-5)=42 | | 10x^2+7x-12= | | w^2+8w-15=0 | | 4x-7=4(x-2)-2 | | x^4-13x^2+12=0 | | 7-(w-4)+2(w-3)=6w-5 |

Equations solver categories